Age Metastereotypes and the Content of Imagined Interage Conversations. (March 2021) - Fowler, Craig; Gasiorek, Jessica
Study 1 ( n = 475) employed an established experimental technique to investigate whether there were implications of metastereotypes for the communicative nature of interage interactions (IAIs) imagined by participants. Activating positive (rather than negative) metastereotypes indirectly predicted anticipated communicative outcomes of IAIs via positive affect, but only when participants personalized metastereotypes. Effect sizes were smaller than expected on the basis of previous research, however, and a second study was conducted to examine why this might be. Study 2 drew on a sample of 446 participants aged 18 to 30 years and compared the degree to which beliefs that older adults positively stereotyped young adults varied as a function not only of the valence of the metastereotype manipulation but also of how metastereotypes were manipulated. Specifically, the manipulation employed in Study 1 was compared against three alternatives. Results yielded support for the superiority of two of the alternative manipulations.